1999
DOI: 10.1590/s0066-782x1999000400006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and identification of sites of chagasic ventricular tachycardia by endocardial mapping

Abstract: Objective -To study electrophysiological characteristics that enable the identification and ablation of sites of chagasic tachycardia. Methods -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Fibrosis and reentry are the most important substrates and mechanisms for VT in that group, respectively 2,27 . The CMRI with the DE technique provides an excellent correlation with fibrosis 18,19 , including the identification of the inflammatory process due to CCM via endocardial biopsy 28 .…”
Section: Substrate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Fibrosis and reentry are the most important substrates and mechanisms for VT in that group, respectively 2,27 . The CMRI with the DE technique provides an excellent correlation with fibrosis 18,19 , including the identification of the inflammatory process due to CCM via endocardial biopsy 28 .…”
Section: Substrate Analysismentioning
confidence: 99%
“…Ventricular tachycardia (VT) is a common complication of chagas' cardiomyopathy (CCM), resulting from ventricular fibrosis and dysfunction [1][2] . Up to 70% of the patients with CCM have sudden cardiac death (SCD) (annual mortality rate between 0.2% and 19.2%) 1,[3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophysiological study with programmed ventricular stimulation was performed in all patients, according to stimulation techniques previously reported [10][11][12][13] , using up to 3 extrastimuli with a minimum coupling of 200ms, under 2 cycles of basal stimulation (600 and 450ms) [10][11][12][13] . The patients were classified according to the presence (group I) or absence (group II) of syncope during clinical presentation of sustained ventricular tachycardia.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus can lead to the impairment of the epicardial coronary arteries and of the microcirculation, which, in patients with CD, have already been previously affected. Recent studies have shown that T. cruzi-infected diabetic rats die at a higher rate, and have a change in the metabolism of adipose cells, suggesting that, although very initially, inflammation in that tissue could be related to the development of cardiopathy 192 .…”
Section: Diabetes Mellitusmentioning
confidence: 99%